2014
DOI: 10.1371/journal.pone.0105531
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Regulation of Olfactory Transduction and Adaptation in the Olfactory Cilium

Abstract: Olfactory adaptation is a fundamental process for the functioning of the olfactory system, but the underlying mechanisms regulating its occurrence in intact olfactory sensory neurons (OSNs) are not fully understood. In this work, we have combined stochastic computational modeling and a systematic pharmacological study of different signaling pathways to investigate their impact during short-term adaptation (STA). We used odorant stimulation and electroolfactogram (EOG) recordings of the olfactory epithelium tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 143 publications
(238 reference statements)
1
16
0
Order By: Relevance
“…The n Hill and K 1/2 obtained by fitting the dose-response curve of activation of CaM as a function of free [Ca 2+ ] ([Ca 2+ ] free ) ( Fig. 1C ) were in accordance with published values 22 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The n Hill and K 1/2 obtained by fitting the dose-response curve of activation of CaM as a function of free [Ca 2+ ] ([Ca 2+ ] free ) ( Fig. 1C ) were in accordance with published values 22 .…”
Section: Resultssupporting
confidence: 89%
“…To reproduce physiological changes of [Ca 2+ ], two buffers were simulated, an unspecific buffer (UB) and CaM. We simulated CaM according to its structure composed by two distinct domains, each one containing a pair of Ca 2+ -binding sites 22 . We validated the model of association of Ca 2+ to CaM by fitting a dose-response curve with the Hill equation:…”
Section: Resultsmentioning
confidence: 99%
“…When we analyzed moderate impact SNVs, the variety of gene families in which they occur is wide, drawing attention to the olfactory receptors family, which had high representation. These genes, involved in the Olfactory Signaling pathway, act in the perception of odor through olfact, interact with odorant molecules in the nasal epithelium, to initiate a neuronal response that triggers the perception of a smell (Antunes et al 2014). The biochemical signaling events related to this (super pathway) act in food recognition and consequently food preference (Ma 2007), identi cation of sexual partners (Kang et al 2015), mother-infant bonding (Doucet et al 2009) and several other aspects of animal survival.…”
Section: Selection Of Genes Containing High and Moderate Effects Snvsmentioning
confidence: 99%
“…From there, the signal is sent on to the hypothalamus and other regions in the brain. Experiments in the mouse have indicated that fluctuations in the level of secondary messengers, which in part are controlled by cyclases and phosphodiesterases, influence the way in which signals from odour-binding receptors are transferred (178) . Cilia-based olfactory defects may also relate to changes in the grey matter of the brain as shown by Braun et al (167) .…”
Section: Sensory Cilia For Odour Perceptionmentioning
confidence: 99%